2014
DOI: 10.1111/jopr.12171
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Crown‐to‐Implant Ratio on Stress Around Single Short‐Wide Implants: A Photoelastic Stress Analysis

Abstract: MT conical short-wide implants showed higher stress values that were distributed through a higher area directed to the implant apex. The C/I ratio influences the stress distribution only under oblique loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 16 publications
2
19
1
2
Order By: Relevance
“…This may interfere with fatigue of prosthetic abutments and also result in more MBL. 30,74 In the present review, this relationship was not found because in the study by Pohl et al 71 there was lower bone loss (0.44 mm) and higher crown-to-implant ratio (1.86) compared to the study by Rossi et al 40 which presented more MBL (0.54 mm) with a crown-to-implant ratio of 1.49 for short implants. Recent studies have shown that there is no relationship between the highest crown-to-implant ratio and the highest MBL.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…This may interfere with fatigue of prosthetic abutments and also result in more MBL. 30,74 In the present review, this relationship was not found because in the study by Pohl et al 71 there was lower bone loss (0.44 mm) and higher crown-to-implant ratio (1.86) compared to the study by Rossi et al 40 which presented more MBL (0.54 mm) with a crown-to-implant ratio of 1.49 for short implants. Recent studies have shown that there is no relationship between the highest crown-to-implant ratio and the highest MBL.…”
Section: Discussioncontrasting
confidence: 51%
“…29 Thus, the short implant has been gaining more credibility, although it may still present a risk of mechanical failure due to a discrepancy in the crown-to-implant ratio, which in turn may be compensated by a wide diameter. [30][31][32] There is still a controversy regarding the classification of short implants. Short implants were classified as those < 10 mm.…”
Section: Maxillarymentioning
confidence: 99%
See 1 more Smart Citation
“…However, these techniques are associated with increased postoperative morbidity, higher costs, and higher risks of complications during patient rehabilitation [5,7]. Thus, short implants are used, which are considered to be simpler and more effective for rehabilitating atrophic ridges later [8].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also state that increasing the CIR does not have significant effect on marginal bone loss [37][38][39][40]. Yet, some authors claim that keeping this ratio under 1.7 is mandatory to avoid complications [41] while others state that the most of the issues are encountered only when an high CIR is associated with implant tilting or cantilevers [42,43]. FEA suggests that the differences in maximum stress both in the surrounding bone and implant components when increasing the CIR is significant (an approximate 50% increase between 1:1 and 1:1.5) [44,45].…”
Section: Discussionmentioning
confidence: 99%